Comparison of a twin interlocking derotation and compression screw cephalomedullary nail (InterTAN) with a single screw derotation cephalomedullary nail (proximal femoral nail antirotation): a systematic review and meta-analysis for intertrochanteric fractures - Leo Nherera; Paul Trueman; Alan Horner; Tracy Watson; Alan J. Johnstone (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background Intertrochanteric hip fractures are common and devastating injuries especially for the elderly. Surgical treatment is the optimal strategy for managing intertrochanteric fractures as it allows early rehabilitation and functional recovery. The relative effects of internal fixation strategies for intertrochanteric fracture after operation remain limited to relatively small studies which create uncertainty in attempts to establish evidence-based best practice. Methods We conducted a systematic review and meta-analysis of randomised controlled trials (RCTs) and observational studies to assess the clinical effectiveness of two commonly used intramedullary devices: a twin screw integrated cephalomedullary nail (InterTAN) versus a single screw cephalomedullary nail (proximal femoral nail antirotation) in patients with intertrochanteric fractures. The following outcomes were considered: revisions, implant-related failures, non-unions, pain, Harris Hip Score and intraoperative outcomes. Odds ratios or mean differences with 95% confidence intervals in brackets are reported. Results Six studies met the inclusion criteria, two randomised controlled trials and four observational studies enrolling 970 patients with mean age of 77 years, and 64% of patients were female. There was a statistically significant difference (p value < 0.05) for revisions OR 0.27 (0.13 to 0.56), implant-related failures OR 0.16 (0.09 to 0.27) and proportion of patients complaining of pain OR 0.50 (0.34 to 0.74). There was no difference in non-unions and Harris Hip Score (p value > 0.05). There was a significant difference in blood loss and fluoroscopy usage in favour of PFNA, whilst no difference in operating times were observed between the two devices. Conclusions Our meta-analysis suggests that a twin screw integrated cephalomedullary nail InterTAN is clinically more effective when compared to a single screw cephalomedullary nail proximal femoral nail antirotation resulting in fewer complications, fewer revisions and fewer patients complaining of pain. No difference has been established regarding non-unions and Harris Hip Score. Intraoperative outcomes favour PFNA with less blood loss and fluoroscopy usage. Further studies are warranted to explore the cost-effectiveness of these and other implants in managing patients with intertrochanteric fractures.